Supply chain performance evaluation in the presence of undesirable products: A case on power industry - Mojgan Pouralizadeh; Aliraza Amirtaimoori; Rossana Riccardi; Mohsen Vaez-Ghasemi (AIMS Energy, 2020)
One of the most serious problems in electricity supply chain management is excessive energy consumption in oil and gas fields and power plant sections and the control wasted energy or power losses in transmission and distribution lines. The resource allocation and utilization to environmental preservation of pollution gas emissions play a fundamental role in the implementation progress of energy and power plant sections and transmission and distribution lines in the power industry. In fact, the purpose of this study is to examine the effects of activity level control to flare gas reduction and environmental protection in energy and power plant sections and power losses management in an electricity supply chain. In other words, this study proposes a DEA model for evaluating electricity supply chain management to sustainability and environmental preservation in economic activity. A real case on the Iran power industry is presented to demonstrate the applicability and practicability of the proposed method. To demonstrate the capability of the proposed approach, this framework is implemented for the performance evaluation of a supply chain identified by oil and gas companies, power plants, transmissions companies, dispatching companies and final consumers in Iran. One empirical implication has obtained from the model performance. As the results show approximately, power plants have earned efficient more than 80% of the total in supply chains but oil and gas fields need to make their efforts to reduce pollution substance emissions by flare gas recovery and putting out oil fields burners. Also, the results demonstrate excessive wasted energy in the transmission and distribution lines as they need to engineer workforce to power loses abatement. Besides, this study recommends that the energy, power plant, transmission and distribution networks should be equipped with improved engineering systems and specialist workforce to economic boom increase and energy losses abatement and environment preservation from industrial pollutions.